Rural speech-language pathologists' perceptions of working with allied health assistants. (December 2013) - O'Brien, Rachael; Byrne, Nicole; Mitchell, Rebecca; Ferguson, Alison
Abstract Workforce shortages are forecast for speech-language pathology in Australia, and will have a more significant impact on rural and remote areas than on metropolitan areas. Allied health (AH) disciplines such as physiotherapy and occupational therapy address the problem of workforce shortages and growing clinical demand by employing allied health assistants (AHAs) to provide clinical and administrative support to AH professionals. Currently, speech-language pathologists (SLPs) don't work with discipline-specific allied health assistants in all states of Australia (e.g., New South Wales). This paper aims to provide insight into the perceptions of SLPs in one Australian state (NSW) regarding working with AHAs. Semi-structured interviews were conducted with eight rural SLPs. Qualitative analysis indicated that participants perceived they had deficits in skills and knowledge required to work with AHAs and identified further training needs. Participants perceived the SLP role to be misunderstood and were concerned about poor consultation regarding the introduction of AHAs into the profession. Ambivalence was evident in overall perceptions of working with AHAs, and tasks performed. While previous research identified benefits of working with AHAs, results from this study suggest that significant professional, economic, and organizational issues need addressing before such a change should be implemented in speech-language pathology.